Effect of Salinity on The Absorption of Metal Pb in Blood Cockle (Anadara granosa) - Purnama, Indra Dwi Putra; Siregar, Yusni Ikhwan; Amin, Bintal (Jurnal Perikanan dan Kelautan, 2018)
Blood cockle interact with physical and chemical oceanography factors caused by the tides intensely, so it’s not possible to blood cockle to free from heavy metal pollution. As a organisms, blood cockles are relatively sedentary and filter feeder, so that the presence of pollutants in the marine waters will be absorbed by the biota. Research on the absorption of metal (Pb) with different salinity level and shell size was conducted in August 2017. It aims to determine the ability of Pb absorption in blood cockle based on salinity level and shell size differences. The method used is experimental method using Factorial Randomized Block Design which is designed from 2 factors namely salinity and shell size. The absorption of Pb by blood cockles were higher at 20 o/oo compared to 25 o/oo, as well as the uptake by 3 cm shells length of the cockles were higher than that by the cockles with 4.5 cm length.